Search costs and corporate income tax competition - Kai A. Konrad (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper studies corporate tax competition if it is costly to learn some of the elements that determine the effective tax burden. Search cost may, but need not, eliminate the tax competition pressure. The outcome depends on the boundaries of tax rate and tax base choices. Search cost can explain the empirically observed tax cuts cum base broadening.
Keywords: H70; H87; 330; costly search; tax competition; corporate taxation; monopoly pricing paradox; Unternehmensbesteuerung; Steuerwettbewerb; Steuerplanung; Informationskosten; Monopolistischer Wettbewerb; Steuertarif; Steuerbemessung; Theorie